Influence of planting methods and time of earhing up on yield nutrient uptake and balance in ginger (Zingiber officinale) - SHAIKH, A A; GHADAGE, H L; JAWALE, S M (The Indian Journal of Agricultural Sciences, 2011)
An experiment wvas conducted during 2003-2004 to study effect of different planting methods (flat bed, ridges and furrows and raised bed) and 3 times of earthing up (3,4 and 5 months after planting) of ginger (Zingiber officinale L.) on yield, nutrient uptake and balance in ginger. Significantly increased green rhizome yield in ginger is obtained where ginger was grown on flat bed (20.34 tonnes/ha) as compared to raised bed (16.29 tonnes/ha) and ridges and furrows.(12.73 tonnes/ha). An earthing up given to ginger at 4 months after planting gave significantly higher green rhizome yield (19.10 tonnes/ha) compared with the earthing up at 3 (14.33 tonnesl ha) and 5 months after planting (15.94 tonnes/ha).